Strategies occupational therapists employ to facilitate work-related transitions for persons with hand injuries: a study protocol for a scoping review - Michelle Elizabeth Uys; Helen Buchanan; Lana Van Niekerk (BMJ Open, 2019)
Introduction Hands make it possible to be employable and productive, to communicate non-verbally and to perform fine motor tasks required in day-to-day activities. Sustaining a hand injury can be detrimental to function including the ability to work. As the literature on work-related transitions is scattered across a range of journals, it is difficult to get a sense of how much literature there is, what is known and where the gaps lie. This scoping study will provide a single source of up-to-date evidence to inform health professionals about the strategies occupational therapists employ to facilitate work-related transitions for people with hand injuries.Methods and analysis The methodological framework by Arksey and O’Malley (2005) will form the structure of the scoping review. The search strategy has been developed in collaboration with a subject librarian. The following databases will be searched: EBSCOhost including only Medline, CINAHL and Health Source: Nursing/Academic Edition; PubMed, Scopus, The Cochrane library and Web of Science. Reference lists will be examined, and grey literature sources will be searched to ensure that literature missed in the database searches is included. Covidence will be used to manage the project. Full-texts will be uploaded for literature that meets the inclusion criteria. A process of blind review will be used to ensure that consistency and rigour is upheld.Ethics and dissemination The findings of the scoping review will be disseminated in an article, within 2019, to be published in a peer-reviewed journal. The findings will be presented at conferences to ensure the optimal dissemination of the scoping review’s conclusions.